A research of DC motor dual close-loop PID speed-tuning system on the basis of ABC Algorithm - Dongshan Geng; Kunyi Chen; Yongchao Yang; Shaowu Li; Qing Ai (Chinese Control and Decision Conference, 2014)
This thesis, subject to the obstacles exist throughout the process of tuning and optimization of the prevailing DC Double close-loop PID controller parameters, explains to realize the tuning and the optimization of PID controller parameters by introducing the Artificial Bee Colony Algorithm on the basis of Nectar Collecting Behavior to the DC Double close-loop tuning system. The comparison and the analysis, processed by step response between the consequences of the Artificial Bee Colony Algorithm and Engineering Methods, indicate that the improved Artificial Bee Colony Algorithm can help us obtain a better dynamic performance index, and a faster following behaviors and robustness, due to which a practical and more comprehensive method to optimizing PID parameters is discovered;.